Does renewable energy reduce energy intensity? A matter of income inequality - Rongrong Li; Zhuang Yang; Qiang Wang (Humanities & Social Sciences Communications)
Abstract This study investigates the complex relationships between income inequality, renewable energy utilization, and energy efficiency across 104 countries from 2010 to 2020. By employing the Panel Threshold Model and Unconditional Quantile Regression based on the Re-centered Influence Function, the analysis focuses on the moderating role of income inequality in shaping the impact of renewable energy consumption on energy intensity. The results indicate a nonlinear relationship, driven by a single-threshold effect of income inequality. In contexts with low income inequality, renewable energy consumption significantly reduces energy intensity, demonstrating its potential to enhance energy efficiency. However, as income inequality increases, this positive association weakens, suggesting that income inequality can act as a barrier to achieving energy-efficient economies. The study further highlights substantial variations across regions and income levels. In high-income economies, greater financial resources enable more widespread adoption of renewable energy, mitigating the adverse effects of income inequality on energy efficiency. By contrast, in middle-income countries, severe income disparities erode the ability of renewable energy to contribute meaningfully to reducing energy intensity. These findings suggest that by incorporating equity considerations into energy strategies, nations can strengthen the synergy between renewable energy adoption and energy efficiency, fostering progress across diverse economies.